ECONOMIC INDICATORS OF SURGICAL TREATMENT OF ATHEROSCLEROSIS OF THE FEMORAL-POPLITEAL SEGMENT IN PATIENTS FOR CRITICAL LIMB ISHEMIA - O.A. Holyachenko (State Institution of Science «Research and Practical Center of Preventive and Clinical Medicine» State Administrative Department, 2021)
Introduction: is to analyze the economic indicators of different types of surgical treatment of atherosclerosis of the femoral-popliteal segment of the lower extremity in patients for сritacal limb ishemia.